2014
DOI: 10.1016/j.spinee.2013.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar surgery in work-related chronic low back pain: can a continuum of care enhance outcomes?

Abstract: Background Context Systematic reviews of lumbar fusion outcomes in purely workers’ compensation (WC) patient populations have indicated mixed results for efficacy. Recent studies on lumbar fusions in the WC setting have reported return-to-work rates of 26–36%, re-operation rates of 22–27%, and high rates of persistent opioid use two years post-surgery. Other types of lumbar surgery in WC populations are also acknowledged to have poorer outcomes than in non-WC. The possibility of improving outcomes by employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Because relatively few studies exist examining risk factors for poor lumbar fusion outcomes among the WC population, 4-5 , 8 , 12 we wanted to examine how psychosocial factors, chiefl y depression, impact lumbar fusion outcomes in a WC setting. WC patients tend to have worse lumbar fusion outcomes and lower postoperative RTW rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Because relatively few studies exist examining risk factors for poor lumbar fusion outcomes among the WC population, 4-5 , 8 , 12 we wanted to examine how psychosocial factors, chiefl y depression, impact lumbar fusion outcomes in a WC setting. WC patients tend to have worse lumbar fusion outcomes and lower postoperative RTW rates.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] A 2010 case-control study reported that WC subjects, when compared with the general population, had signifi cantly less improvement in mean Oswestry Disability Index and 36-Item Short Form Health Survey scores after fusion. [1][2][3][4][5][6][7] A 2010 case-control study reported that WC subjects, when compared with the general population, had signifi cantly less improvement in mean Oswestry Disability Index and 36-Item Short Form Health Survey scores after fusion.…”
mentioning
confidence: 99%
“…116 After multidisciplinary rehabilitation for back pain, opioid dependent patients were less likely to return to work and more likely to seek new sources of care. 117 It is unclear whether these problems result from the pharmacologic effects of opioids, characteristics of patients most likely to receive them, or some combination. …”
Section: Interference With Other Treatmentsmentioning
confidence: 99%
“…[52] Among patients with work-related injuries, preoperative depression and preoperative opioid dependence have been associated with higher postoperative medical costs, lower return to work rates, lower work retention rates, and longer postoperative pain medication use compared to other patients. [53,54] Although additional research is needed to develop and evaluate the efficacy of specific strategies to improve perioperative outcomes, conducting a holistic evaluation of every patient should enable nurses to recognize psychological and social barriers to recovery.…”
Section: Pseudarthrosismentioning
confidence: 99%